Peptidomic Characterization of < 3 kDa Peptides from Milk Fermented by Lactic Acid Bacteria: Sequence-Based Antimicrobial Prediction and In Vitro Immuno-Oncological Evaluation - Ozturk, Hale Inci; Kiran, Fadime; Ekiz, Melis Sardan; Celikbicak, Omur; Ozturkoglu-Budak, Sebnem (SPRINGER, 2026)
This study investigated the production of low-molecular-weight peptides (< 3 kDa) from milk proteins by endemic lactic acid bacteria strains and examined the effects of strain type, fermentation, and storage time on functional peptide formation to identify promising bioactive peptides and their producer strains for targeted functional dairy applications. To achieve this, < 3 kDa peptide fractions obtained from fermented milk with various LAB strains were characterized using LC-QTOF-MS. The highest peptides numbers were identified in samples fermented with Lactobacillus (Lb.) helveticus. beta-casein-derived peptides predominated due to its high abundance in milk and flexible structure, which makes it more susceptible to proteolysis by LAB enzymes. This facilitates extensive peptide release during fermentation, and many of these fragments possess known antimicrobial activities, explaining their strong contribution to antibacterial potential. In vitro antibacterial activities were also assessed, and peptide sequences were scored for antibacterial potential using a Random Forest model. Random Forest analysis indicated that beta-casein derived peptides were the main contributors to antibacterial potential. Serum albumin was hydrolyzed to a greater extent compared to other whey proteins. <3 kDa peptide fractions demonstrated inhibitory activity only against the Gram-negative bacteria Salmonella (S.) Typhimurium and Escherichia (E.) coli. The anticancer activities of the peptide fractions were evaluated against colorectal (HT-29), hepatocellular (Hep-G2), and breast (MCF-7) cancer cell lines, along with their immunomodulatory effects on RAW 264.7 macrophages. Anticancer activity was observed to be dose-dependent across all tested cell lines, with the most pronounced inhibitory effect generally detected at 50 & micro;g/mL (p < 0.05). Peptide fractions derived from L. paraplantarum showed the strongest inhibitory effects against all tested cancer cell lines. Although no significant increase was observed in IL-12 and IL-6 levels, peptide fractions from L. paraplantarum and Lb. helveticus 11B2, enhanced TNF-alpha production in macrophages, indicating a controlled activation of macrophage-mediated innate immune responses that may contribute to antitumor immunity. This study demonstrates a clear strain-dependent divergence in peptide bioactivity, with L. paraplantarum NCCB 100,523 being associated with stronger anticancer and immunomodulatory effects, while Lb. helveticus 12B1 and Lb. helveticus 11B2 were linked to enhanced antibacterial activity, indicating their practical relevance for the targeted design of bioactive peptides and the development of functional foods with specific biological functions.
Keywords: Caseins; Serum proteins; Functional peptides; AMP; TNF-alpha; Anticancer; BOVINE BETA-CASEIN; PROTEOLYTIC ACTIVITY; LACTOBACILLUS-HELVETICUS; DAIRY-PRODUCTS; ANTIBACTERIAL; PROTEINASE; MICROBIOTA; Biotechnology & Applied Microbiology; Microbiology